Time-variable gravity field recovery from reprocessed GOCE precise science orbits - Grombein, Thomas; Arnold, Daniel; Jäggi, Adrian (2021)
The satellite mission GOCE (Gravity Field and Steady-State Ocean Circulation Explorer) observed the Earth's gravity field between November 2009 and October 2013 with an unprecedented accuracy and a high spatial resolution. While the core instrument for gravity field measurements was a three-axis gravity gradiometer, two dual-frequency GPS receivers were used as primary instruments for orbit and low-degree gravity field determination. In this presentation, we focus on the capability to recover time-variable gravity field signals from the collected GOCE GPS data. For this purpose, we use the GPS-based kinematic positions of the reprocessed GOCE precise science orbits (PSOs) that have been computed at the Astronomical Institute of the University of Bern (AIUB) in the framework of the GOCE reprocessing campaign. Using these kinematic positions as pseudo-observations for gravity field recovery with the celestial mechanics approach, we estimate spherical harmonic coefficients of the Earthâ?Ts (static) gravity field up to degree and order (d/o) 120, and simultaneously solve for trends and annual periodic signals of the time-variable gravity field up to d/o 10. As shown by previous studies, gravity field determinations based on the reprocessed GOCE PSOs provide a substantially improved quality for the lower spherical harmonic degrees compared to those derived from the operational PSOs that suffer from ionosphere-induced artifacts along the geomagnetic equator. We demonstrate that (1) the use of the reprocessed GOCE PSOs, and (2) the inclusion of the GOCE common-mode accelerometer data as part of the force model, are crucial to exploit the full potential of the time-variable gravity field signal captured by the GOCE satellite. Although the GOCE GPS data cover only a relatively short time period of about four years, our analyses show that it is possible to recover the major time-variable signals, for example in Greenland and Antarctica. To assess the quality of the estimated trends and annual periodic signals, we compare ...